1992
DOI: 10.1111/j.1944-9720.1992.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Foreign Language Proficiency‐Based Testing in Secondary Schools

Abstract: As foreign language education moves toward proficiency‐based teaching and testing, few studies have looked systematically at its effects on student performance, classroom methods and materials, teacher expectations, and program administration, particularly at the secondary level. The study reported here examines the effects of district‐wide ACTFL Oral Proficiency Interview (OPI) testing. Specifically, the study asks, “Do students who perform well on the OPI also perform well on more traditional measures of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 15 publications
10
36
1
Order By: Relevance
“…The OPI ratings for Level 2 in this study were comparable to those revealed in Huebner and Jensen's (1992) study in which the majority of students in Level 2 Spanish were rated from Novice Mid to Novice High. The Level 4 ratings in the present study, however, were somewhat lower than those obtained in Huebner and Jensen's study in which the majority of Level 4 Spanish students were rated Intermediate Mid.…”
Section: Requirementsupporting
confidence: 82%
See 2 more Smart Citations
“…The OPI ratings for Level 2 in this study were comparable to those revealed in Huebner and Jensen's (1992) study in which the majority of students in Level 2 Spanish were rated from Novice Mid to Novice High. The Level 4 ratings in the present study, however, were somewhat lower than those obtained in Huebner and Jensen's study in which the majority of Level 4 Spanish students were rated Intermediate Mid.…”
Section: Requirementsupporting
confidence: 82%
“…'This dual notation represents a rater discrepancy. Huebner and Jensen (1992) also tentatively concluded that students who develop more advanced oral proficiency skills do not suffer, relative to their peers, in the development of other FL skills as indicated by more traditional measures of FL achievement.…”
Section: Notesmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Steinmeyer (1984) and Huebner and Jensen (1992) report very low numbers (fewer than 5) of informants at some class levels. Due to a number of limitations discussed below, these studies provide only rough estimates of representative OPI scores in relationship to length of instruction.…”
Section: Previous Studiesmentioning
confidence: 95%
“…Median scores provided in parentheses. Median scores inHuebner and Jensen (1992) calculated from tabled data in original.…”
mentioning
confidence: 99%